Tau Oligomers: The Toxic Player at Synapses in Alzheimer’s Disease - Guerrero-Muñoz, Marcos J.; Gerson, Julia; Castillo-Carranza, Diana L. (Frontiers in Cellular Neuroscience, 2015)
Alzheimer’s disease (AD) is a progressive disorder in which the most noticeable symptoms are cognitive impairment and memory loss. However, the precise mechanism by which those symptoms develop remains unknown. Of note, neuronal loss occurs at sites where synaptic dysfunction is observed earlier, suggesting that altered synaptic connections precede neuronal loss. The abnormal accumulation of amyloid-β (Aβ) and tau proteins is the main histopathological feature of the disease. Several lines of evidence suggest that the small oligomeric forms of Aβ and tau may act synergistically to promote synaptic dysfunction in AD. Remarkably, tau pathology correlates better with the progression of the disease than Aβ. Recently, a growing number of studies have begun to suggest that missorting of tau protein from the axon to the dendrites is required to mediate the detrimental effects of Aβ. In this review we discuss the novel findings regarding the potential mechanisms by which tau oligomers contribute to synaptic dysfunction in AD.